Unpacking the Role of Teacher Competence and Collaborative School Culture in Primary Education: A Systematic Review - Baroroh, Umi; Bunyamin; Sudana, I Made (Journal of Innovation and Research in Primary Education, 2025)
This study aims to systematically examine how professional teacher competence and collaborative school culture contribute to improving instructional quality in primary education. Utilizing a Systematic Literature Review (SLR) approach, the study analyzed 40 peer-reviewed journal articles from the Scopus database published between 2020 and 2025. The findings reveal four key dimensions of teacher competence that significantly impact instructional quality: adaptive pedagogy, content mastery and assessment literacy, digital literacy, and reflective professional practice. These dimensions form a cohesive ecosystem that enables teachers to design meaningful, inclusive, and future-oriented learning experiences. Furthermore, the study identifies four essential dimensions of collaborative school culture: shared vision and distributed leadership, engagement in professional learning communities (PLCs), peer-coaching and collaborative planning, and a psychologically safe school climate. These cultural elements create a sustainable environment for collective growth and innovation in teaching practices. The integration of teacher competence and school-level collaboration fosters transformative teaching and positions schools as reflective learning communities. This review provides both conceptual insights and practical implications for policy and professional development programs aimed at enhancing instructional quality. The findings highlight the need for a dual-focus strategy that simultaneously empowers individual teachers and strengthens collaborative structures to ensure sustainable educational transformation